Towards the development of affective recognition using heart sound signal: a proposal - Suryady, Zeldi; Abdul Rahman, Abdul Wahab; Handayani, Dini Oktarina Dwi (IEEE, 2022)
In recent years, the development of physiologicalbased human emotion is centred around the use of Electroencephalogram (EEG) as the main modality. However, heart sound signal (also referred to as Phonocardiography) offers unique and reliable advantages to infer emotions. As one of the physiological parameters, heart signals may infer emotions and can be used for emotion recognition. In addition, the use of heart sound signals for emotion recognition is substantially cheaper, and the process of acquiring the signal for heart sound analysis is comfortable as compared to other physiological measures. Nevertheless, the use of Phonocardiography (PCG) in the emotion recognition domain is still scarce in the research literature. Therefore, this work conducts a review on affective computing in general and discusses how emotions are described and the common procedure used to elicit emotion. We also highlight how far the PCG has been used in the domain of affective computing. Finally, we propose the framework and methodology to develop human emotion recognition using heart sound signals.